Oscillation of Generalized Second-Order Quasi Linear Difference Equations - Srimanju, V.; Khadar Babu, Sk.; Chandrasekar, V. (International Journal of Engineering and Technology, 2018)
Authorsipresent sufficienticonditions for theioscillation of the generalizediperturbed quasilinearidifferenceiequation  where , and . Examplesiillustrates the importanceiof our results are alsoiincluded.